Effects of silybin on growth performance, antioxidant capacity and immunity in juvenile hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) fed with high-lipid diets - Mingsheng Xie; Hao Liu; Weibin Huang; Menglong Zhou; Shuang Zhang; Beiping Tan; Shuyan Chi; Yuanzhi Yang; Xiaohui Dong (Aquaculture Reports)
This research examined the impacts of varying silybin dosages in high-lipid diets on the growth, hepatic histology, immunity, and immune-related gene expression of juvenile hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂). The grouper (with an initial body weight of 8.27 ± 0.08 g) were fed diets containing silybin at levels of 0 g/kg (S1, control group), 0.05 g/kg (S2), 0.10 g/kg (S3), 0.15 g/kg (S4), 0.20 g/kg (S5), 0.25 g/kg (S6), and 0.50 g/kg (S7) for 8 weeks. The study results suggest that the silybin-treated groups displayed an initial increase followed by a decrease in final body weight and specific growth rate, with the highest value observed in the group S5. In serum samples, silybin supplementation of high-lipid diets resulted in increased activities of alkaline phosphatase (AKP), superoxide dismutase (SOD) and catalase (CAT) enzymes, decreased activities of aspartate transaminase (AST) and alanine transaminase (ALT) enzymes and increased total antioxidant capacity (T-AOC) content. In liver, the addition of silybin to high-lipid diets increased SOD, CAT, and lysozyme (LYZ) enzyme activities, increased T-AOC and immunoglobulin M (IgM) contents, and decreased reactive oxygen species (ROS) and malondialdehyde (MDA) contents. Contrasted with the control group, the addition of silybin at 0.05–0.50 g/kg enhanced the hepatic histomorphology, for example, ameliorating the indistinctness of cell outlines and diminishing the hepatocyte vacuolation. Silybin treatment significantly upregulated the expression of liver sod, cat, gpx, nrf2, keap1, hsp70, hsp90, tlr22, myd88, il-1β, tnf-α and il-6(P < 0.05). Silybin treatment significantly upregulated the expression of tlr22, myd88, il-1β, tnf-α, and il-6 of head kidney (P < 0.05). After vibrio harveyi challenge, groups S5-S6 showed higher survival than the control. Incorporating silybin into high-lipid diets boosts grouper's growth, antioxidant, and immune abilities. Regression analysis implies adding 0.23 g/kg silybin to the diets of juvenile hybrid grouper.